Lean Six Sigma in policing services: case examples, lessons learnt and directions for future research. (3rd April 2019) - Antony, Jiju; Rodgers, Bryan; Cudney, Elizabeth A.
Abstract : This paper reports the use of Lean Six Sigma (LSS) in Policing Services, Scotland and the authors present four case examples of LSS and the key lessons learnt from such projects. Public services in the UK are under significant budget pressures and require to optimise efficiencies to maintain quality of service to the public. Our findings suggest that LSS methodology can be embraced by Policing Services to create not only efficient and effective processes at reduced operational costs but also increase the morale of employees and develop a better engaged workforce within the Police community and through this maintain and improve quality of service. The paper also illustrates some of the most commonly used tools in LSS projects. This paper finally seeks to contribute to and broaden the limited body of evidence of the applicability of LSS to Police Services and suggests future directions for research. In the authors' opinion, this is possibly one of the first studies reporting the benefits of LSS in any Policing Services. The paper yields an immense value to senior managers in any public sector who are engaged in any form of continuous improvement initiatives to achieve and sustain a competitive advantage. The results of the study add evidence to the general arguments on the applicability of LSS to the public sector but more specifically evidence the potential of the methodologies in policing and through this assist to fill a current research gap.